Proposal for the revision of guidelines for clinical trials of vaccines to prevent infectious diseases in Japan. Issue 43 (12th October 2022) - Nomura, Yumiko; Noda, Kiyohito; Oohashi, Yuusuke; Okuda, Shin; Matsumoto, Jun; Nakano, Takashi; Tsuchida, Nao; Ishii, Ken J.; Hayashi, Kunihiko; Iiyama, Tatsuo; Onodera, Hiroshi; Ishii, Koji; et al.
Highlights: We propose the revision of the infectious disease vaccine clinical trial guidelines. New vaccines should be evaluated for the protective efficacy with multiregional clinical trials. In non-major subjects, immunogenicity should be compared with that of main subjects. Abstract: The development of vaccines against infectious diseases requires a different approach from that of therapeutics, because vaccines are inoculated into healthy individuals and have a preventive effect by activating the immunity of the inoculated human. In Japan, "The Guideline for Clinical Trials of Vaccines for the Prevention of Infectious Diseases" was published in 2010 before changes occurred in the vaccine development environment in Japan, such as the introductions of foreign vaccines and simultaneous global development. This study aimed to identify current challenges in vaccine development through a questionnaire-based survey of pharmaceutical companies in Japan and by comparing the domestic and international guidelines and surveying review reports of 35 vaccines approved in Japan between April 2010 and December 2020. Identified challenges included the requirement for protective efficacy trials, efficacy evaluation of combination vaccines, development of multiregional and foreign clinical trials, and immunization of older adults and immunocompromised patients. We propose that new vaccines against infectious diseases should be evaluated for the protective efficacy, preferably through multiregional clinical trials. Additionally, differences in the incidence of infectious diseases or in epidemic virus strains between regions may affect the trials, when multiregional clinical trials are conducted, but immunogenicity-based studies can be conducted if a correlation between protective efficacy and immunogenicity has been established. We suggest that licensed combination vaccines can be used as comparators when an antigen is added to a licensed combination vaccine. We also proposed that the efficacy of a vaccine in non-major subjects, such as older adults or immunocompromised patients could be evaluated by comparing immunogenicity in major subjects with the confirmed protective effects of the vaccine. It is expected that these revisions will lead to the rapid advancement of vaccine development, which should contribute to the improvement of public health.